Contexts of empirical research in the social sciences - Brzeziński, Jerzy Marian (Człowiek i Społeczeństwo, 2016)
The article analyses “immersing” empirical research conducted in the field of social sciences (psychology, sociology, education etc.) in four contexts: psychological, ethical, cultural and the context of methodological awareness. It focuses in particular on the following issues, crucial for the condition of social sciences: – research competences of those who undertake to design and conduct empirical research (the state of social and individual methodological awareness); – specificity of psychological research carried out with the participation of human subjects – the perception of empirical research as an interaction “researcher – participant of the study”; – cultural specificity of the environment in which research takes place; – attitude of researchers towards research participants (the state of ethical awareness); – accepted patterns of disseminating research results (the policy of editors of scientific journals to approve only of such papers which contain statistically significant results i.e. with significance at the level of p < 0,05;; – assessment practices applied in institutions employing researchers: bibliometric assessment of academic units and the evaluation of individual scholars’ research performance; – succumbing to the pressure exerted by supervisors on researchers to publish “at all costs.”